Equity pricing New Keynesian models with nominal rigidities and investment - Nath, R (University of Oxford, 2018)
This paper derives explicitly an equity pricing relationship in a simple New Keynesian model. This relationship is used to study the equity pricing implications of New Keynesian models. I ?nd that New Keynesian models su?er from the same asset pricing shortcomings as more traditional RBC versions and that this can be attributed to the presence of nominal rigidities. I then add capital adjustment costs to study how the interaction of both investment adjustment costs and capital adjustment costs a?ect the results.